Upaya Mewujudkan Program Sustainable Development Goals (SDGs) dalam Membangun Kualitas Pendidikan Indonesia - Anggiasti, Avita Ayu; Nugraheni, Nursiwi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Currently, government programmes already include high-quality education. The government is not the only entity trying to improve education. Private institutions, educational organizations, and the general public are also involved in this effort. This document aims to gather information as part of an effort to realize the Sustainable Development Goals Programme (SDGs) in the context of improving the quality of education in Indonesia. This research uses a qualitative research approach with a descriptive approach. The findings from literary reviews, academic articles, and previous research on this topic served as the basis for discussion. The study reveals the potential for improving the quality of education in Indonesia and identifies factors that contribute to its low quality. Teachers need to engage in professional development activities to relevant learning goals in the classroom and improve the quality of education. When a focus on pedagogy is required, it involves leadership, supervision, and guidance to ensure that established quality standards are met in best educational practices..